PERUMUSAN STRATEGI BISNIS PADA MY GREEN LAUNDRY MALANG - Hendry Khoeswandy Kho (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The objective of this study is to determine the application of business strategy formulation at My Green Laundry. This study describes the internal and external environment of the research object, from which the role of Porter’s five forces strategy, EFE & IFE and SWOT matrix, IE Matrix, and QSPM Matrix that are used to analyze company are identified. The results show the threat of replacement products that poses a major threat to laundry business people. Therefore, anticipative strategies are required. The bargaining power of suppliers has a little effect on the business, while bargaining power of consumers holds an important force, requiring the company to improve its service quality. The internal strength of Green Laundry is that the company prioritizes quality, washes according to customer’s request, does not charge delivery cost, opens earlier, and closes later. The weaknesses of this company are that the company charges too high, does not do sufficient promotional activities, does not have any website, and makes its employees to have multiple task so that they cannot focus on one job. A viable strategy for the Laundry, based on the QSPM matrix, is market penetration. Keywords: Porter’s five force strategy , EFE and IFE analysis, SWOT analysis, IE matrix, QSPM matrix